Conformational stability and crystal packing: polymorphism in Neurospora crassa CAT‐3. Issue 7 (22nd July 2013) - Zárate‐Romero, Andrés; Stojanoff, Vivian; Rojas‐Trejo, Sonia Patricia; Hansberg, Wilhelm; Rudiño‐Piñera, Enrique
<x xml:space="preserve">Abstract</x> Polymorphism is frequently observed from different crystallization conditions. In proteins, the effect on conformational variability is poorly documented, with only a few reported examples. Here, three polymorphic crystal structures determined for a large‐subunit catalase, CAT‐3 from Neurospora crassa, are reported. Two of them belonged to new space groups, P1 and P43212, and a third structure belonged to the same space group, P212121, as the previously deposited 2.3 Å resolution structure (PDB entry 3ej6), but had a higher resolution (1.95 Å). Comparisons between these polymorphic structures highlight the conformational stability of tetrameric CAT‐3 and reveal a distortion in the tetrameric structure that has not previously been described.